Legal Strengthening of Credit Agreement Based on Information Technology in Financial Technology Companies in Supporting Industry 4.0 - Ramlan Ramlan (RIRAI Publisher, 2021)
Changes in the pattern of lending and borrowing also experienced growth over the development period. From a system that manually switches to digital. Since the existence of general information, technology-based credit services have been quite good in supporting industry 4.0, but there are still problems such as high-interest rates, and there are several debtor rights violated that need to be discussed regarding legal arrangements and legal strengthening. The research method is the type of normative legal research, how to collect data from library research and analysis of data with qualitative analysis. The results showed that financial technology regulation is regulated in the OJK Law, ITE Law, POJK, and PBI, and concerning legal reinforcement is needed for the problem of high-interest rates to debtors, electronic agreement standard clauses, threats, defamation, and violating customer privacy so that they can attract more many investors in supporting industry 4.0 with the use of financial technology, because the problem is only still regulated in the ITE Law has not been specifically applied in the implementation of financial technology.